2016
DOI: 10.1016/j.ophtha.2015.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Topical Fluorometholone Protects the Ocular Surface of Dry Eye Patients from Desiccating Stress

Abstract: Three-week topical 0.1% fluorometholone therapy is effective not only in reducing ocular surface signs in DED patients, but also especially in preventing exacerbation caused by exposure to a desiccating stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 35 publications
1
47
0
2
Order By: Relevance
“…Topical steroids have a role for treating keratoconjunctivitis sicca (KCS), as outlined in the Tear Film and Ocular Surface Society Dry Eye Workshop II (TFOS DEWS II) report . This report summarizes the currently available evidence on managing dry eye disease, including results from several RCTs, and concluded that short courses of corticosteroid are effective in improving symptoms of KCS. However, this is not an effective long‐term strategy due to potential side effects.…”
Section: Uses Of Locally Administered Steroidsmentioning
confidence: 99%
“…Topical steroids have a role for treating keratoconjunctivitis sicca (KCS), as outlined in the Tear Film and Ocular Surface Society Dry Eye Workshop II (TFOS DEWS II) report . This report summarizes the currently available evidence on managing dry eye disease, including results from several RCTs, and concluded that short courses of corticosteroid are effective in improving symptoms of KCS. However, this is not an effective long‐term strategy due to potential side effects.…”
Section: Uses Of Locally Administered Steroidsmentioning
confidence: 99%
“…172174 Therapies targeting the acute effects of desiccation would likely provide more rapid relief of eye irritation and prevent the effects of a dry, drafty environment such as an airplane cabin. Corticosteroids have shown efficacy in treating chronic dry eye and preventing irritation and cornea barrier disruption in response to a desiccating environmental challenge 175178 ; however, long-term use of corticosteroids carries risks of cataract formation and glaucoma, and therapies with steroid-like inhibitory effects on innate inflammatory pathways would represent a major advance.…”
Section: Future Directions For Researchmentioning
confidence: 99%
“…110,111 Topical treatment with 0.1% dexamethasone for 2 weeks prior to a low-humidity exposure stress using specially designed goggles significantly decreased corneal and conjunctival staining, improved blink rate and decreased Human leukocyte antigen -D related (HLA-DR) RNA levels in conjunctiva of patients with aqueous deficient dry eye. 112 Significant improvement in signs and symptoms of dry eye were observed after 3 weeks of topical 0.1% fluorometholone therapy in dry eye patients subjected to a 2-hour challenge in a controlled adverse environment exposure, 113 which increases the concentrations of MMP-9 and other inflammatory markers in tears. 114 …”
Section: Corticosteroidsmentioning
confidence: 99%